Konflik Etno-Religius' di Indonesia Kontemporer Dalam Pandangan Orde Baru - Imam Iqbal (TASAMUH: Jurnal Studi Islam, 2017)
Indonesia is destined to be a pluralistic country, both in terms of race, language, customs and religion. Conflicts nuances of ethnic, religious, racial, and inter-group (SARA) is one of the most vicious forms of violence. Historical development of Indonesian nationality colored nuances SARA number of conflicts. SARA nuanced conflict in the archipelago have taken place since the colonial era. Even the issue of SARA is pre-colonial heritage, typical Malay who has been there before Indonesia existed. Similarly, in the early days of independence in the days of the Old Order, conflicts SARA already surfaced. However, in two days, SARA issues arise naturally as a cultural dynamics of society. Unlike the two previous times, the regime tried to suppress racial issues systematically. During the New Order, brought up the issue of SARA into illicit goods into categories considered subversive by the government would be a source of division and disintegration of the nation. The New Order regime has been successful in establishing uniformity in all areas of life, so at that time, this nation seems to be a nation that is quiet, safe, but without real life. The New Order regime disclaims any form of turmoil in any small community, let alone the nuances SARA. Similar upheavals suppressed and hidden in dark corners are not covered by the public browse binoculars. By basing itself on the concept of state integrality, New Order imagined as a large family and the citizens should live in harmony and peace in harmony, harmony and balance. Unity in a unified equation is much more preferred than the difference diverse divisions that opened the gap. Various differences in aspirations and interests of social groups, ethnic and religious pressed discharged to the surface, for the sake of unity in the family of nations Indonesia.